2021
DOI: 10.3390/mi12101171
|View full text |Cite
|
Sign up to set email alerts
|

An Effective SARS-CoV-2 Electrochemical Biosensor with Modifiable Dual Probes Using a Modified Screen-Printed Carbon Electrode

Abstract: Due to the severe acute respiratory syndrome coronavirus (SARS-CoV-2, also called coronavirus disease 2019 (COVID-19)) pandemic starting in early 2020, all social activities ceased in order to combat its high transmission rate. Since vaccination combats one aspect for halting the spread of the virus, the biosensor community has looked at another aspect of reducing the burden of the COVID-19 pandemic on society by developing biosensors that incorporate point-of-care (POC) testing and the rapid identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Apart from the conventional antibody/antigen-based receptors, aptamers (i.e., oligonucleotides) and ACE2 (i.e., human angiotensin-converting enzyme 2) have also been utilized to develop the SARS-CoV-2 electrochemical biosensors. Regarding the former, we found five individual studies that used an aptamer receptor to target different SAR-CoV-2-related biomarkers, including the S1 receptor-binding domain (RDB) [ 52 , 53 ], RNA sequence [ 54 , 55 ], and nucleocapsid protein (NP) [ 27 ] ( Table 2 ). On the other hand, we also found five individual studies that adopted ACE2 as their receptors (or used it as an alternative to the secondary antibodies).…”
Section: Aptamer and Ace2 Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the conventional antibody/antigen-based receptors, aptamers (i.e., oligonucleotides) and ACE2 (i.e., human angiotensin-converting enzyme 2) have also been utilized to develop the SARS-CoV-2 electrochemical biosensors. Regarding the former, we found five individual studies that used an aptamer receptor to target different SAR-CoV-2-related biomarkers, including the S1 receptor-binding domain (RDB) [ 52 , 53 ], RNA sequence [ 54 , 55 ], and nucleocapsid protein (NP) [ 27 ] ( Table 2 ). On the other hand, we also found five individual studies that adopted ACE2 as their receptors (or used it as an alternative to the secondary antibodies).…”
Section: Aptamer and Ace2 Receptormentioning
confidence: 99%
“…In many real cases, this feature may become more dispositive than other critical technical performances because the distribution of the point-of-care testing kits depends heavily on precisely coordinated cold-chain logistics, and the less temperature-sensitive aptamer-based biosensors can remarkably ease the burden on the logistical cost. After carefully reading all the SARS-CoV-2 electrochemical aptasensors, we found that four (i.e., 80% of total aptamer-based studies) had undergone sensor stability tests over different time spans at 4 °C (or storage in a refrigerator) [ 27 , 52 , 53 , 55 ]. Among them, Abrego-Martinez et al [ 53 ] reported an outstanding result in the thermal stability test after 21-day storage at 4 °C, in which the impedimetric response of the developed aptasensor only lost 1% of its sensing capability with respect to the freshly prepared one.…”
Section: Aptamer and Ace2 Receptormentioning
confidence: 99%
“…A dual probe-based amplification-free electrochemical sensing approach was proposed by Pang et al for enhanced sensitivity detection of the SARS-CoV-2 nucleic acid sequence, in which the SPCE electrodes were modified with ssDNA capture probe using streptavidin/biotin and EDC/NHS chemistry, and the mimicked sample sequence was functionalized with FITC detector probe on which an anti-fluorescein antibody (HRP) tag was added [78]. For detection, the SPCE containing the dual probe-attached sample sequence was dipped in a solution of 3,3 ,5,5 -tetramethylbenzidine (TMB) and H 2 O 2 , which generated a current signal to be measured by chronoamperometry method using an Autolab.…”
Section: Isothermal Nucleic Acid Amplification Tests (Inaats)mentioning
confidence: 99%
“…In Section 3.2, enzyme-based biosensors are reviewed, while in Section 3.3, the discussion related to the non-enzymatic biosensors has been included. Glucose sensor [82] Glucose, glutamate, lactate sensor [83] pH sensor [84] Uric Acid sensor [85] Dopamine detection [86] SARS-CoV-2 [87,88] MERS-CoV [89] Escherichia coli (E. coli) [90] Inkjet Printing Multianalyte (pH, Protein, Glucose) sensor Drop-on-demand (DOD), maskless, can create patterns on non-planar surfaces, well-defined patterning, simple, capacity for mass production [91] Nozzle clogging, highly specified ink formulation, limited resolution Ammonia sensor [92] Pathogen detection [93] Bienzymatic Glucose biosensor [94] Calorimetric sensor/ H 2 O 2 detection [95,96] H 2 O 2 and glucose detection [97] Pressure ulcer detection [98] Wearable biosensor detection system/norovirus detection [99] HIV-related ssDNA detection [100] Multiplexed biosensor [101] Protein detection [102] SARS-CoV-2 detection [103] Table 1. Cont.…”
Section: Introductionmentioning
confidence: 99%